Pneumonectomy for broncho-pulmonary carcinoids: a single centre analysis of surgical approaches and patient outcomes - Diotti, Cristina; Bertolaccini, Luca; Girelli, Lara; Uslenghi, Clarissa; Donghi, Stefano Maria; Guarize, Juliana; Spada, Francesca; Fazio, Nicola; Spaggiari, Lorenzo (Frontiers in Oncology, 2024)
Background Pneumonectomy is a radical surgical procedure associated with significant morbidity and mortality. Its application in the context of pulmonary neuroendocrine tumours, including carcinoid tumours, requires meticulous preoperative planning and intraoperative precision. This study aims to assess the safety and efficacy of pneumonectomy in the management of these rare and challenging neoplasms. Methods A retrospective analysis of patients who underwent pneumonectomy for pulmonary carcinoid tumours at our institution over a specified period was conducted. Data regarding patient demographics, tumour characteristics, surgical techniques, intraoperative complications, perioperative management, and long-term outcomes were collected and analysed. Results Between March 2001 and October 2022, 21 patients (7 male, 14 female) with carcinoid tumours underwent pneumonectomy on a total of 459 surgical operations for carcinoid. Preoperative bronchoscopic procedures were conducted in 90.4% of cases, leading to histological diagnoses for most. The median hospital stay was eight days, with no reported perioperative deaths. Median follow-up after surgery was 73 months, with a five-year overall survival of 65.4 months. Recurrences occurred in 28.6% of cases, primarily in atypical carcinoids. Conclusion Despite the rarity of bronchial carcinoids, pneumonectomy is effective for low-grade malignancies, demonstrating positive short—and long-term outcomes. Radical lymph node dissection is fundamental in pathological staging and overall survival.